The Universality of metaphor in art - Ospina Herrera, Carlos Alberto (Estudios de Filosofía, 2010)
This paper will defend the universality of metaphor in art (Arthur Danto), against those who think (Davidson, Carrol, Vilar) that in art the attribution of expressive properties is literal and not metaphorical. The thesis that the artistic metaphor operates as a tensive symbol that points to meanings (epiphora) and at the same time creates presence (diaphora). Thanks to both elements art creates presence, creates reality or trans gurates the usual and gives it the sudden and amazing possibilities of presence, to which the spectator corresponds not only with the senses, but also with affection, understanding and imagination.